Using chemical and ecotoxicological approaches to assess the ecological risk of pollutants in the Cananeia-Iguape Estuarine Complex, SP, Brazil - Cruz, Ana Carolina Feitosa (2014)
This study aimed to study the quality of sediments of the Cananéia-Iguape-Peruíbe estuarine complex (CIP) by using chemical and ecotoxicological analysis, in order to determine if metals from sediments would be bioavailable to benthic organisms. The different tools show that the estuary exhibits signs of alteration due to contamination by metals, which, in their turn, have their origin in mining activities situated upstream of Ribeira de Iguape River. Toxicities were attributed to metals and ammonia suggesting that the combination of natural and anthropic factors may be capable of producing ecological risks. Additionally, this study evidenced that depositional areas appear to move along the estuary, accompanying the displacement of the maximum turbidity zone, which in its turn depends on the freshwater inputs associate to seasonality. These results highlight that oceanographic processes should be considered as important factors that influence on the accumulation of contaminants in estuarine areas. The bioaccumulation test confirmed that these contaminants may be bioavailable to the organisms, especially in the more contaminated sites, and therefore, may be transferred to the food chain, with implications to ecological processes and human health.